Preparation and Antibacterial Activity of New Azo-Schiff Thiazol Ligand and Some of its Metal Complexes - Eateman Salah Mahdi; Raheem Tahir Mahdi Al-Sa'edi (Nano Biomedicine and Engineering, 2018)
New chelate compounds, with general formula [M(HL1)2](H2O)2, M = Co(Ⅱ), Ni(Ⅱ), Cu(Ⅱ)] and [M(HL1)2](H2O), M = Zn(Ⅱ), Cd(Ⅱ), Hg(Ⅱ), were prepared by reacting chlorid salt of these metals with the new azo Schiff-base ligand 4-((E)-(3-bromo phenyl)diazenyl)-2-((E)-(thiazol-2-ylimino) methylphenol HL1 using the coupling of diazonium salt of 3-bromoaniline with (E)-2-(thiazol-2-ylimino) methyl phenol. The new azo Schiff thiazol ligand and its chelate complexes were characterized by available spectra and analytical methods such as mass spectra, proton nuclear magnetic resonance (1H-NMR), infrared (IR) spectroscopy, ultraviolet-visible spectroscopy (UV-Vis), elemental analysis (CHN), molar conductivity and magnetic susceptibility measurements. Results showed that the ratio of metal: ligand was 1:2, and also showed that Co(Ⅱ), Ni(Ⅱ), and Cu(Ⅱ) chelate complexes had octahedral geometry, while Zn(Ⅱ), Cd(Ⅱ) and Hg(Ⅱ), had tetrahedral geometry. The ligand with its complexes was tested in vintor against the sensitive organisms, including Staphylococcus aureus (gram positive) and Pseudomonas aeruginosa (gram negative). The study showed that the prepared metal complexes had more biological affectivity than the ligands themselves.